Mediating role of self-esteem on the relationship between mindfulness, anxiety, and depression. (July 2016) - Bajaj, Badri; Robins, Richard W.; Pande, Neerja
Abstract: The current study aimed to examine the mediation effects of self-esteem on the association between mindfulness and anxiety and depression. A sample of 417 undergraduate students completed a packet of questionnaires that assessed mindfulness, self-esteem, anxiety, and depression. Correlation results indicated that mindfulness was associated with self-esteem, anxiety, and depression. Using Structural Equation Modeling (SEM), mediational analyses showed that mindfulness exerted its indirect effect on anxiety and depression through self-esteem. A multi-group analysis showed that the mediational model was not moderated by gender and thus provided a preliminary support for the robustness of the final meditational model. The findings corroborate an important role of self-esteem in mindfulness exerting its beneficial effects on anxiety and depression. Highlights: Mindfulness predicted anxiety and depression Mindfulness predicted self-esteem Self-esteem partially mediated the mindfulness-anxiety relationship Self-esteem partially mediated the mindfulness-depression relationship